2017
DOI: 10.1111/apa.14138
|View full text |Cite
|
Sign up to set email alerts
|

National study shows that abusive head trauma mortality in Sweden was at least 10 times lower than in other Western countries

Abstract: The risk of unreported fatal AHT in Sweden was low, and there may have been cases misdiagnosed as AHT. The at least 10 times lower incidence than has been reported from other Western countries, raises the question if previously reported higher incidences of fatal AHT have been exaggerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
11
1
1
Order By: Relevance
“…The diagnostic criteria for abusive head trauma (AHT) and its attributes have been widely debated. This national study investigated the possibility of false‐positive and false‐negative cases of fatal AHT in Sweden . Andersson and Thiblin evaluated the records of 733 infants who died up to the age of 365 days and were examined from 1994 to 2013 at the country's six forensic medicine departments.…”
Section: Lower Rate Of Fatal Abusive Head Trauma In Sweden Than In Otmentioning
confidence: 99%
“…The diagnostic criteria for abusive head trauma (AHT) and its attributes have been widely debated. This national study investigated the possibility of false‐positive and false‐negative cases of fatal AHT in Sweden . Andersson and Thiblin evaluated the records of 733 infants who died up to the age of 365 days and were examined from 1994 to 2013 at the country's six forensic medicine departments.…”
Section: Lower Rate Of Fatal Abusive Head Trauma In Sweden Than In Otmentioning
confidence: 99%
“…In a national study covering a 20‐year period, the authors were unable to identify any infant with SDH without perinatal risk factors, significant disease or findings consistent with nonimpact head trauma. Moreover, the authors of this study raised the question that previously reported higher incidence of fatal AHT in other Western countries has been exaggerated.…”
mentioning
confidence: 81%
“… results fuelled the discussion and widened the differences, involving influential medical societies and leading to the publication of numerous responses both in support and in disagreement . Notably, one of the studies that followed reported a low incidence of AHT in Sweden. In a national study covering a 20‐year period, the authors were unable to identify any infant with SDH without perinatal risk factors, significant disease or findings consistent with nonimpact head trauma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study based on the records of the National Board of Forensic Medicine in Sweden together with death certification records for the period 1994–2013 inclusive, Andersson and Thiblin have attempted to identify all infants with a probable diagnosis of AHT. They conclude that amongst the infants whose deaths were certified as being due to sudden infant death syndrome (SIDS) (all of whom underwent forensic autopsy including examination of the central nervous system), there were no deaths from AHT.…”
mentioning
confidence: 99%